PENERAPAN MANAJEMEN ASET UNTUK MENINGKATKAN KINERJA JARINGAN IRIGASI (STUDI KASUS: DAERAH IRIGASI KEDUNG PUTRI, KABUPATEN NGAWI, JAWA TIMUR) - Devara, Kevin; Wahyuni, Sri; Prayogo, Tri Budi (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p04, 2020)
The main factor to maintain the fulfillment of food needs is by increasing agricultural harvest. Good management of irrigation systems is a solution to increase agricultural harvest. Therefore, a study is required to implement asset management.  The aim of this study is to apply asset management to improve irrigation network performance in Kedung Putri irrigation area in Ngawi Regency, East Java . This study requires irrigation network inventory data, which is used as input in analyzing irrigation asset performance, in ranking the condition of irrigation assets, and for non-parametric statistic tests. The irrigation assets are the physical infrastructure of the irrigation network. This study utilized the Criteria and Weighting of Irrigation Network Performance Assessment of 2018, which had been modified in accordance with the needs of the study. In addition, the utilized statistical tests were the Kruskal-Wallis test and the Mann-Whitney test because the obtained data were in the form of ranks. The results of this study showed that 50.4% of irrigation assets in very good condition, 27.8% in good condition, 20.9% in moderate condition, and 0.9% in poor condition. In addition, the highest ranking (rank 1) was for the Paron Secondary Channel and the lowest ranking (rank 114) was for railroad bridge B.KT.3h, railroad bridge B.BS.2b, and railroad bridge B.DW.1f. Data analysis through statistical testing (Kruskal-Wallis test) showed that H (6.431) ? X (0.05;6) (12.592), and thus the statistical conclusion of the proposed hypothesis is that there is no difference, meaning H0 is accepted and H1 is rejected. This shows that the correlation between the results of the Kruskal-Wallis test and the relationship between ranks and condition score, as well as the results of the assessment of the hydraulic structure and the channel is appropriate, being that there were no differences from each group.